Memories of Pre-Jurassic Lost Oceans: How To Retrieve Them From Extant Lands - Isozaki, Yukio (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
The information reflected in midoceanic sedimentary deposits provides critical constraints for reconstructing past global environmental changes. Available data from extant oceans, however, are limited to the Early Jurassic and younger ages, because older oceanic plates have been subducted. This article explains methods for obtaining information on pre-Jurassic mid-oceanic conditions by conducting fieldwork on older orogenic belts exposed on land. The key point is the identification of ancient accretionary complexes (AC), not along currently active margins but within older orogenic belts in continental domains, particularly by recognizing ocean plate stratigraphy (OPS) that contains midoceanic strata, as demonstrated by studies of on-land exposed ancient AC in Japan and elsewhere. In this paper, six examples of retrieved mid-oceanic sedimentary data are introduced, in which significant records on the following unique events in the pre-Jurassic world are archived: 1) the extinction- related Paleozoic–Mesozoic boundary superanoxia (based on data from the Jurassic AC in SW Japan); 2) the Permian Kamura cooling event in the mid-Panthalassa (ditto); 3) the Neoproterozoic snowball Earth evidence from the mid-Iapetus Ocean (based on data from the Neoproterozoic–Cambrian AC in Wales, UK); 4) the discovery of enigmatic Ediacaran (Neoproterozoic) microfossils from a midoceanic atoll complex (based on data from the Cambrian AC in southern Siberia, Russia); and 5) and 6) Early Archean (3.8 and 3.5 Ga) biogenic signatures in mid-oceanic deep-sea environments (based on data from the Eoarchean AC at Isua in Greenland, and the Paleoarchean one in Pilbara, Western Australia). These results demonstrate the great utility of OPS analysis for understanding pre-Jurassic lost oceans, including the early biological and environmental evolution of the globe.